Implementasi Kesetaraan Gender dalam Pemenuhan Hak Pendidikan Siswi Hamil sebagai Korban Diskriminasi Institusional - Cindy Santika (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2025)
This study analyzes the implementation of gender equality in fulfilling the educational rights of pregnant students who experience institutional discrimination in North Lampung Regency. Discriminatory practices remain systematic, evident in exclusive school policies, gender-biased attitudes from teachers and peers, and the absence of effective reintegration programs. The study aims to identify forms of institutional discrimination faced by pregnant students and to develop a gender-responsive, human rights–based protection model. Using a normative legal method with both legal-political and conceptual approaches, this research reviews national regulations, international instruments, and relevant academic literature. The findings indicate that discrimination against pregnant students is inconsistent with substantive justice and violates constitutional guarantees under the 1945 Constitution and Law No. 20 of 2003 on the National Education System. The novelty of this research lies in proposing a protection model that integrates a Human Rights-Based Approach and Gender Mainstreaming through affirmative measures such as a Regional Regulation on Inclusive Education for Pregnant Students, the establishment of a Youth-Friendly Counseling Unit, and reintegration mechanisms in formal and non-formal education. This model is expected to promote a more inclusive, responsive, and gender-sensitive educational system while guiding local governments in strengthening protections for young women who experience pregnancy.